Labor Drops : Experimental Evidence on the Return to Additional Labor in Microenterprises - de Mel, Suresh; McKenzie, David; Woodruff, Christopher (World Bank, Washington, DC, 2017)
The majority of enterprises in many developing countries have no paid workers. This paper reports on a field experiment conducted in Sri Lanka that provided wage subsidies to randomly chosen microenterprises to test whether hiring additional labor would benefit such firms. In the presence of labor market frictions, a short-term subsidy could have a lasting impact on firm employment. Using 12 rounds of surveys to track dynamics four years after the end of the subsidy, the study finds that firms increased employment during the subsidy period, but there was no lasting impact on employment, profitability, or sales. Two supplementary interventions and treatment heterogeneity suggest the lack of impact is not due to complementarities with capital or management skills, and detailed survey data help rule out a number of theoretical mechanisms that could result in sub-optimally low employment. The study concludes that the urban labor market facing microenterprises does not have large frictions that would prevent own-account workers from becoming employers.